Late- Pleistocene Wedge Structures Along The Patagonian Coast (Argentina): Chronological Constraints And Palaeo-Environmental Implications - Ribolini, Adriano (2014)
This paper investigates several wedge structures formed in continental deposits covering marine sediments deposited during MIS 5 along the central Patagonian coast of Argentina. The size and surface microtexture characteristics of the infilling sediments are consistent with a depositional environment dominated by aeolian transport. Fragments of Andean volcanic rocks (glass shards) in the wedge-fill suggest long-distance transport via a westerly component of wind direction. The wedges are interpreted as products of deep seasonal frost action in frozen ground, which produced open cracks that filled rapidly with partially non-local aeolian sediments. Many wedges cross cut carbonate crusts that formed under permafrost conditions in coastal Patagonia. The radiocarbon dating of carbonate crusts yielded an age of 25–27 kyrbp, while wedge-fill sediments are OSL dated to 14 670 ± 750 yrbp. This indicates that ground wedge formation occurred during a cold event (the Antarctic Cold Reversal period) that interrupted the permafrost degradation following the Last Glacial Maximum.